Chapter 3 Allergic to Innovation? Dietary Change and Debate about Food Allergy in the United States - Smith, Matthew (Bloomsbury Academic, 2018)
This chapter investigates how allergists and their patients have understood the relationship between dietary change and allergy during the twentieth century. Industrial food production and the emergence of a global food economy provided both challenges and, possibly, explanations for food allergy sufferers and their physicians. As the production of food became further removed geographically from consumers during the course of the twentieth century, it became more difficult for food allergy sufferers to identify harmful allergens, thus making accidental exposure more likely. But many allergists also suspected that some of the ingredients used in food processing - especially maize and synthetic food dyes - were also potent allergens. Although such ideas were contested, they also mirrored deeper concerns about escalating rates of autoimmune disease. The chapter argues that, rather than dismissing such ideas out of hand, we should engage with them more deeply in the hope of explaining why such diseases are on the rise.